Perseverative Thinking in Depression and Anxiety - Sorg, Sonja; Vögele, Claus; Furka, Nadine; Meyer, Andrea H. (Frontiers in Psychology, 2012)
The current study investigated the impact of worry and brooding as moderators of the tripartite model of depression and anxiety (TMDA). We hypothesized that both types of perseverative thinking would moderate the association between negative affectivity (NA) and both anxiety and depression. Complete data sets for this questionnaire survey were obtained from 537 students. Participants’ age ranged from 16 to 49 years with a mean age of 21.1 years (SD = 3.6). Overall, results from path analyses supported the assumptions of the TMDA, in that negative affectivity was a non-specific predictor for both depression and anxiety whilst lack of positive affectivity was related to depression only. Unexpectedly, perseverative thinking had an effect on the dependency of negative and positive affectivity. Worry was a significant moderator for the path NA – anxiety. All other hypothesized associations were only marginally significant. Alternative pathways as well as methodological implications regarding similarities and differences of the two types of perseverative thinking are discussed.